التكوين أثناء الخدمة ودوره في تحسين أداء الموظفين بالمؤسسة الجزائرية - داسي, عائشة; فايزي, سهيلة (University of Eloued جامعة الوادي, 2023)
الملخص: هدفت هذه الدراسة إلى معرفة دور التكوين أثناء الخدمة في تحسين أداء الموظفين في المؤسسة الاقتصادية اتصالات الجزائر لولاية الوادي. وتمثلت اشكالية الدراسة في السؤال التالي: -هل للتكوين أثناء الخدمة دور في تحسين أداء الموظفين؟ وتندرج ضمنه الفرضيات التالية: - محتوى التكوين اثناء الخدمة دور في تحقيق الرغبات المهنية للموظفين. -لبرامج التكوين دور في تحسين أداء الموظفين. - للعملية التكوينية أثر إيجابي على أداء الموظفين. -للتكوين دور في تحقيق فعالية الأداء لدى الموظفين. أهداف الدراسة: - الكشف عن مدى مساهمة التكوين أثناء الخدمة في تلبية الاحتياجات المعرفية للموظفين في المؤسسة الاقتصادية. - التعرف على مدى فاعلية أداء الموظفين في المؤسسة الاقتصادية أثناء التكوين. - معرفة الأساليب المتبعة في عملية التكوين أثناء الخدمة. منهج الدراسة: تم الاعتماد على المنهج الوصفي في هذه الدراسة. المجال المكاني والزماني للدراسة: وتم إجراء الدراسة الميدانية في المؤسسة الاقتصادية وكالة اتصالات الجزائر لولاية الوادي في السنة الجامعية 2022/2023، من شهر جانفي إلى 14 ماي 2023. عينة الدراسة: تم استخدام العينة القصدية التي قدر ب 30 موظف، وتم جمع البيانات بواسطة الاستمارة كأداة رئيسية لجمع البيانات والتي احتوت على أربع محاور رئيسية: المحور الاول: محتوى التكوين المحور الثاني: برامج وأساليب التكوين المحور الثالث: تقييم العملية التكوينية المحور الرابع: أداء العاملين وكانت عينة الدراسة التي قدر عددها ب 30 موظف وكانت العينة قصدية. النتائج - يؤدي التكوين الى تعزيز الثقة والرضا الوظيفي للموظفين ومساعدتهم على مواجهة التحديات وتحقيق النتائج. - لبرامج التكوين دور هام في تحسين أداء الموظفين في المؤسسة وذلك من خلال زيادة الفاعلية والكفاءة. - للعملية التكوينية أثر إيجابي على أداء الموظفين من خلال اكسابهم خبرات جديدة. -للتكوين دور في تحقيق فاعلية أداء الموظفين من خلال تطوير مهارتهم. Abstract This study aimed to know the role of in-service training in improving the performance of workers in the economic institution Algeria Telecom in the state of El-Oued. The problem of the study was represented in the following question: Does in-service training have a role in improving employee performance? It includes the following hypotheses - The content of training during the service has a role in achieving the professional desires of the workers. Training programs have a role in improving the performance of workers. The training process has a positive impact on the performance of Works. Training has a role in achieving effective performance among employees. Objectives of the study: Exposing the extent of the contribution of in-service training in meeting the knowledge needs of employees in the economic enterprise. - To identify the effectiveness of the performance of workers in the economic institution during training. - Knowledge of the methods used in the training process during the service. Study Methodology: The descriptive approach was relied upon in this study. The spatial and temporal field of the study: The field study was conducted in the economic institution, the Algeria Telecom Agency, in the state of El Oued, in the academic year 2022/2023, from January to May 14, 2023. Study sample: The intentional sample was used, which was estimated at 30 employees, and the data was collected using the questionnaire as the main tool for data collection, which contained four main axes: The first axis: the content of the composition The second axis: training programs and methods The third axis: evaluation of the formative process The fourth axis: employee performance As well as the interview, and the sample of the study, which was estimated at 30 employees, and the sample was intentional. Results Training leads to enhancing the confidence and job satisfaction of workers and helps them face challenges and achieve results. Training programs have an important role in improving the performance of employees in the organization by increasing effectiveness and efficiency. The training process has a positive impact on the performance of employees by providing them with new experiences. Training has a role in achieving the effective performance of employees by developing their skills.
دراسة ميدانية بمؤسسة اتصالات الجزائر-الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: التكوين، Genèse, Genesis; الأداء الوظيفي، Fonctionnalité, Functionality